Rice productivity growth and instability in selected Southeast Asian countries - Sawaneh, Mamma (2013)
Productivity estimates are indicators of success of any individual firm from one period to another. It gauges the performance of a Decision Making Unit (DMU) for a period of time. This study aims to investigate rice productivity growth as well as measure production instability among five rice producing countries in Southeast Asia from 1980 to 2010. Contextually, a panel data was used to evaluate the Total Factor Productivity (TFP) growth and production instability in the rice sector from 1980 to 2010. The study measures Malmquist productivity indices as well as its decomposition into efficiency change and technical change using non parametric (Data envelopment analysis) approach. It examines the rice productivity growth of five (5) rice producing countries namely; Malaysia, Myanmar, Philippines, Thailand and Vietnam in Southeast Asia from 1980 to 2010. The study utilized linear programing methods to give estimates of distance functions and thus compute Malmquist productivity indices. The study also use statistical tools such as coefficient of variations and variance using SPSS, STATA and MS Excel softwares to evaluate the extent of production instability and the sources of instability in each country. The results indicated that, all the countries with the exception of Malaysia exhibit positive growth in rice productivity over the reference period of 1980 to 2010. A broader examination of total factor productivity in different periods shows that growth was greater in the period 2001-2005. Though on average, the productivity growth in all periods are sustained through technological improvement. The result of this study can now give inferences that there exists efficiency and productivity improvement among rice producing countries in Southeast Asia. However, the differences in the extent of productivity improvement vary from period to period as well as from country to country. In addition to that, the components relating to total factor productivity that is Technical Change (TC) and Efficiency Change (EC), the former turned out to be a more influential source of growth. In reference to production instability, a time series data on rice harvested area, yield and production of the same countries was used to analyze the components of production changes (area, yield and interaction effects) from 1980 to 2010. The production data was categorized into two (2) periods: (i) 1980/81 to 1994/95 and (ii) 1995/96 to 2009/10. The designated two periods in reference to the post Green Revolution, allow for an examination of sources and changes in instability intra and inter the two periods. The results showed that a significant increase in rice production in all countries has been witnessed during the reference period. However the effect of area and yield to increase production differs from one country to another. In Myanmar, mainly due to area increase whereas in others (Malaysia, Philippines, Thailand and Vietnam), yield played a dominant role in increasing rice production. It is worthy mention from this instability study that variability in area, yield and production in all countries (except for Malaysia) were positively related. That is to say their decreasing/increasing trend result in decrease/increase instability. Thus, in these countries, an increase in rice production due to an increase in either area or yield would subsequently increase instability. However, in Vietnam, an increase in yield would further help to reduce production instability. Furthermore, the decomposition analysis indicated that changes in mean yield mainly drove mean production in Malaysia, Philippines, Thailand and Vietnam. However, change in mean area contribution was larger in the case of Myanmar. On other hand, changes in area-yield covariance between periods in the countries made a negligible contribution to the change in rice production. Thus in order to stabilize instability in the region, government policies and programs that increase productivity should be encouraged. These could be done through provision of basic inputs for rice production and also intensifying agricultural research and development in the coming decades. It is hoped that through such programs an increase in mean yield in the countries will be attained thereby stabilizing rice production in the region.